Strategic planning as an instrument of the State planning system in the Republic of Kazakhstan - Soltangazinov, A.; Simonov, S.; Amirovа, M.; Kaidarova, S.; Karimbergenova, M. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The successful development of the socio-economic system depends on many factors, including the quality of the public administration. In the article the main aspects of the use of strategic planning in the system of public administration are described, taking into account the totality of different interests and providing the identification of problematic aspects of territorial development. The purpose of the research is the assessment of the strategic planning in domestic practice. The analysis of the introduction in Kazakhstan of a new management model based on strategic planning, which is one of the important tools for ensuring sustainable development, shows, on the whole, its effectiveness. At the same time, the effective implementation of strategic documents of the state planning system of the Republic of Kazakhstan depends not only on the quality of their development, but is also largely determined by the organizational and economic mechanism, including the monitoring and control system. The results of the study are the identification of certain problematic aspects that impede the integrated use of this tool in the public management system, as well as the developed and proposed practical recommendations aimed at their solution and the economic efficiency of the use and increment of resources for sustainable territorial development.
Стратегиялық жоспарлау Қазақстан Республикасындағы Мемлекеттік жоспарлау жүйесінің құралы ретінде
Стратегическое планирование как инструмент Системы государственного планирования в Республике Казахстан
Keywords: strategic planning; final result; modernization; state planning system; result-oriented budgeting